Effectiveness of Using New Pedagogical Technologies to Increase General and Special Physical Training of Young Players - Musayevich, Umbarov Djuraqul (European Journal of Life Safety and Stability (2660-9630), 2021)
In this article, the selection of players is an important and integral part of the training process, because it helps to solve the main task of sports training, to achieve high sports results. It has also been shown that training has a positive effect on learning outcomes.